2020
DOI: 10.3109/13668250.2020.1827143
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of people with intellectual disability about their family networks: A comparison study with key support worker proxy reports

Abstract: Background: The Family Network Method-Intellectual Disability (FNM-ID) was used to compare perspectives of people with mild intellectual disability and their support workers on family networks of people with intellectual disability. Method: 138 participants with mild intellectual disability and support workers were interviewed, using the FNM-ID. Paired t-tests were used to examine differences in perspectives. Multiple regression analyses were used to examine divergence in perspectives. Results: People with mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
3
1
3
Order By: Relevance
“…The participants in our study defined their connections with family and staff mostly in terms of practical support. This contrasts with prior research, which identified family and staff as important sources of emotional support in the social networks of people with mild intellectual disabilities living in community (Giesbers et al, 2019, 2020; Tournier et al, 2023; Van Asselt‐Goverts et al, 2013, 2015). In this respect, it could be hypothesized that having epilepsy may influence the emotional support needs of people with mild intellectual disabilities and epilepsy.…”
Section: Discussioncontrasting
confidence: 66%
“…The participants in our study defined their connections with family and staff mostly in terms of practical support. This contrasts with prior research, which identified family and staff as important sources of emotional support in the social networks of people with mild intellectual disabilities living in community (Giesbers et al, 2019, 2020; Tournier et al, 2023; Van Asselt‐Goverts et al, 2013, 2015). In this respect, it could be hypothesized that having epilepsy may influence the emotional support needs of people with mild intellectual disabilities and epilepsy.…”
Section: Discussioncontrasting
confidence: 66%
“…La dificultad de conducta y emocionales se asociaron con diferentes perspectivas. (Tournier et al, 2020) Etapa 03 Servicios ambulatorios infantil para discapacitados Este estudio analiza los predictores de la complejidad del servicio en niños con discapacidades del desarrollo intelectual (IDD) y problemas de salud mental comórbidos. Investigamos si el tipo de paciente, los riesgos de seguridad, la carga del trauma y la disfunción familiar estaban asociados con la complejidad del servicio.…”
Section: Etapas Etapa 01 Necesidades Especialesunclassified
“…Porque la gente tiene formas diferentes en que completan las encuestas, también se examina la relación entre las respuestas de los participantes y los métodos para completarla. (Tournier et al, 2020) Etapa 08 Modelado multinivel para discapacitados Los adultos con discapacidad intelectual (DI) a menudo viven en instalaciones residenciales especiales. Los datos recopilados de estos adultos suelen ser complejos.…”
Section: Etapas Etapa 07unclassified
“…Diese Diskrepanz der Sichtweisen könnte bedeuten, dass sie bisweilen mehr Unterstützung erhalten als aus ihrer Sicht notwendig wäre und durch das Abhängigkeitsverhältnis potenziell in ihrer Selbstbestimmung eingeschränkt werden (ebd.). Zu ähnlichen Ergebnissen kommen auch Tournier et al (2020), die einen Unterschied zwischen den Sichtweisen der Menschen mit Beeinträchtigung und ihren Begleitpersonen auf familiäre Netzwerke feststellen und darin mögliche Ursachen für emotionale und Verhaltensprobleme sehen. Eine mögliche Erklärung, weshalb Sichtweisen von Menschen mit kognitiven Beeinträchtigungen noch zu selten berücksichtigt werden, ist, dass deren Erhebung als schwierig gilt und dazu besondere Rahmenbedingungen geschaffen werden müssen.…”
Section: Sichtweisen Von Menschen Mit Kognitiven Beeinträchtigungenunclassified